Religionspädagogik als multidisziplinäre Symbolisierungsdidaktik (Pedagogical Horizons, 2023)
The use of symbols is the central mode of expression of the Christian faith. Believers use them to communicate basic existential convictions. At the latest since the symbolic turn in theology, systematic-reflexive theology has also turned to symbolic modes of expression as a place of understanding faith. The symbolic acts and with them the liturgy of the church have become theologia prima. Because of the corporeality of the human being, the human being itself represents a (real) symbol. Man can only communicate symbolically and also experiences himself as symbolic. In this understanding, religious education as a promoter of education must turn to the symbolic of the human being anew. It is supported in this by the current debate on society and its ‘Resonanzsensibilität‘. In the future, modern Religious Education - not least in the face of a 'culture of the digital' - will have to increasingly engage in constructive Didactics of Symbolisation.
Keywords: Symbols; Religious Education; Liturgy; Resonance